1997
DOI: 10.1136/thx.52.7.628
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fresh fruit consumption on lung function and wheeze in children

Abstract: Abstractcorbate might protect against the lung damage caused by cigarette smoking. 5 However, the Background -Fresh fruit consumption and vitamin C intake have been associated effects are not confined to smokers 1 3 and in one study appeared to be stronger in subjects with improved lung function in adults. Whether this is due to enhancement of lung who had never smoked and to be present in young adults, suggesting that other biological growth, to a reduction in lung function decline, or to protection against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
114
0
7

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(131 citation statements)
references
References 17 publications
10
114
0
7
Order By: Relevance
“…These findings were supported by a plausible biological mechanism, ie an anti-inflammatory effect of the n-3 fatty acids abundantly present in fish oils. In accordance with our findings, all more recent epidemiological studies observed no association of fish intake with COPD related outcomes (Cook et al, 1997;Fluge et al, 1998;Tabak et al, 1999Tabak et al, , 2001aButland et al, 2000). It is not likely that this is due to a higher level of fish intake in the earlier studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings were supported by a plausible biological mechanism, ie an anti-inflammatory effect of the n-3 fatty acids abundantly present in fish oils. In accordance with our findings, all more recent epidemiological studies observed no association of fish intake with COPD related outcomes (Cook et al, 1997;Fluge et al, 1998;Tabak et al, 1999Tabak et al, , 2001aButland et al, 2000). It is not likely that this is due to a higher level of fish intake in the earlier studies.…”
Section: Discussionsupporting
confidence: 92%
“…Cross-sectional studies published in 1990 and 1994 suggested an inverse association between fish consumption and COPD related outcomes . However, all cross-sectional studies published in later years reported negative findings (Cook et al, 1997;Fluge et al, 1998;Tabak et al, 1999Tabak et al, , 2001aButland et al, 2000). In the only individuallevel longitudinal study, no association of fish consumption with 25 y incidence of chronic lung disease was observed (Miedema et al, 1993).…”
Section: Introductionmentioning
confidence: 91%
“…The differences in pulmonary volumes observed between the fifth and the first quintile of TAC were comparable with those reported by others on antioxidant foods (Strachan et al, 1991;Cook et al, 1997;Carey et al, 1998;Butland et al, 2000;Kelly et al, 2003;Nettleton et al, 2009) or vitamins (Schwartz and Weiss, 1994a;Britton et al, 1995;Tabak et al, 1999;Schünemann et al, 2001a, b;Charles et al, 2010) or observed in subjects who developed cardiovascular disease (Schroeder et al, 2005). In particular, the þ 83.4 ml difference in FEV 1 associated with a higher intake of TAC in never smoker premenopausal women was equivalent to an improvement in pulmonary age of 3.3 years.…”
Section: Discussionsupporting
confidence: 73%
“…A consistent body of evidence shows a link between consumption of antioxidant vitamins (Schwartz and Weiss, 1994a;Britton et al, 1995;Tabak et al, 1999;Schünemann et al, 2001a, b;Charles et al, 2010), antioxidant-rich foods (Strachan et al, 1991;Cook et al, 1997;Carey et al, 1998;Butland et al, 2000;Kelly et al, 2003;Nettleton et al, 2009), omega-3 polyunsaturated fatty acids and fish (Schwartz and Weiss, 1994b;Shahar et al, 1994;Sharp et al, 1994;Charles et al, 2010) and better pulmonary function.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary intake of fruits and vegetables may therefore be important in protecting the airway from oxidant and radical air pollutants (48)(49)(50)(51). Epidemiologic studies have shown that a high intake of fruits and vegetables is associated with increased lung function and decreased respiratory symptoms (48)(49)(50)(51).…”
mentioning
confidence: 99%